Role of Exosomes Released by Dendritic Cells and/or by Tumor Targets: Regulation of NK Cell Plasticity - Reiners, Katrin S.; Dassler, Juliane; Coch, Christoph; Pogge Von Strandmann, Elke (Frontiers in Immunology, 2014)
Exosomes are endosomal-derived nanovesicles released by normal and tumor cells, which transfer functionally active proteins, lipids and nucleic acids between cells. They are important mediators of intercellular communication and act on the adjacent stroma as well as in the periphery. Recently, exosomes have been recognized to play a pathophysiological role in various diseases such as cancer or infectious diseases. Tumor cell-derived exosomes (Tex) have been shown to act as tumor promotors by educating non-malignant cells to provide a tumor supporting microenvironment, which helps to circumvent immune detection by the host and supports metastasis. However, Tex with anti-tumor, immune-activating properties were also described reflecting the complexity of exosomes. Here, we assess the role of extracellular microvesicles/exosomes as messengers affecting NK cell function in health and disease and discuss the molecular basis for the differential impact of exosomes on NK cell activity. The molecular composition/load of exosomes and the mechanisms regulating their release remain unclear and need to be further analyzed to facilitate the development of new treatment options targeting the exosomal machinery.